Simulation analysis of AB-BNCT treatment room shielding based on Monte Carlo geometric splitting variance reduction technique - ZHU Yinan; LIN Zuokang; YU Haiyan; YU Xiaohan (He jishu)
BackgroundBoron neutron capture therapy (BNCT) is a new type of binary targeted radiotherapy that is gradually entering the commercial stage. The accelerator-based boron neutron capture therapy (AB-BNCT) neutron sources used in hospitals are inevitably accompanied by neutron leakage and gamma-ray contamination during equipment operation and patient treatment.PurposeThis study aims to analyze the radiation safety of public during the operation of BNCT using Monte Carlo geometric splitting variance reduction technique.MethodsFirstly, based on a 10 mA 2.8 MeV proton accelerator neutron source, the International Commission on Radiological Protection (ICRP) and the basic standard for ionizing radiation protection and radiation source safety in China, GB 18871‒2002 was taken as the reference standard for the annual effective dose limit of 1 mSv for the public. This dose limit was conservatively estimated to be equivalent to a dose rate limit of 0.5 μSv·h-1. Then, a water model with the size of 100 cm×30 cm×80 cm was placed at the outlet of beam shaping assembly (BSA) after neutron beam moderation and collimation, and the shielding calculations of AB-BNCT treatment room were conducted by Monte Carlo programs with various techniques. Finally, these results were comparatively analyzed to give shielding scheme design of the AB-BNCT treatment room, and the optimization design was carried out according to the weak link of the shielding.ResultsThe simulation results indicate that the variance reduction techniques of geometric splitting and Russian roulette for shielding simulation calculations has higher efficiency and achieve more accurate calculation results. After optimizing the shielding design of the BNCT treatment room, the conservative calculation results prove that the total dose rate at the corridor outside the treatment room is less than 0.5 μSv·h-1 when the shielding body is 60 cm thick boron containing heavy concrete, which meets the design requirements. In addition, the thickness range of the boron containing heavy concrete shielding wall required for radioactive workers is given to be 45~50 cm when the dose rate limit is less than 2.5 μSv·h-1.ConclusionsThe shielding design of BNCT treatment room using Monte Carlo geometric splitting variance reduction technique in this study is safe and reliable, providing a theoretical basis for the commercial development of BNCT.